Analysis method of black liquor pyrolysis and gasification using deconvolution technique to obtain the real time gas production profile - Joko Wintoko; Suryo Purwono; Moh. Fahrurrozi; Bambang Soehendro (Jurnal Rekayasa Proses, 2020)
In thermal reaction experiments, e.g., pyrolysis, combustion, and gasification, the gas released from the reaction can be analyzed in gas measuring instruments. There will be some time delay due to the relatively long gas travel from the reactor to the analyzers. Besides, there can be some time lag in the gas measuring instrument. Gas dispersion may furthermore occur and thus alter the gas concentration profile. The observed gas concentration, therefore, can be very different from the original gaseous reaction products profile. A mathematical procedure called deconvolution technique will be used to get the original gaseous reaction products concentrations profile. The deconvolution technique is based on the assumption that original data have been altered by a transfer function to yield observed data. By the deconvolution techniques, the transfer function for each data set will be calculated and then can be used to compute the original data. In this study, the deconvolution technique was applied to the concentration profile of gaseous products from black liquor pyrolysis and gasification reactions measured by gas analyzers instruments to obtain the real-time gas concentration profile during the processes. Tracer gases are injected in the reactor To facilitate the deconvolution calculation, and their concentration profiles observed in the measuring instruments are recorded. Gaseous products that are analyzed are CO2, CO, CH4, SO2, and H2S. This technique can successfully provide the real-time gas production concentration profile from the black liquor pyrolysis and gasification reaction.